Factors that Influence Acquisition of Lower Extremity Braces in the Pediatric Orthopaedic Population. Issue 1 (January 2022) - Rambo, Anna; Rhodes, Leslie; Lomax, Justin; Cao, Xueyuan; Steele, Jack; Romer, Karen; Spence, David; Sheffer, Benjamin W.; Warner, William C.; Sawyer, Jeffrey R.; Kelly, Derek M.
Abstract : Background: Lower extremity brace-wear compliance has been studied in pediatrics, but failure to acquire a prescribed brace has not been included. The purpose of this study was to evaluate brace acquisition as a component of brace-wear compliance. Methods: Records of patients (0 to 21 y) prescribed lower extremity braces from 2017 to 2019 were reviewed. Diagnoses included cerebral palsy, spina bifida, short Achilles tendon, clubfoot, and other. Brace type was categorized as clubfoot foot abduction orthosis, ankle-foot orthosis, knee, hip, or custom/other braces. Brace prescription and acquisition dates were recorded. Insurance was classified as government, private, or uninsured. Patient demographics included age, sex, race, and calculated area deprivation index. Results: Of the 1176 prescribed lower extremity braces, 1094 (93%) were acquired while 82 (7%) were not. The odds ratios (OR) of failure to acquire a prescribed brace in Black and Hispanic patients were 1.64 and 2.71 times that in White patients, respectively (95% confidence interval: 1.01-2.71, P =0.045; 1.23-5.6, P =0.015); in patients without insurance, the OR was 8.48 times that in privately insured patients (95% confidence interval: 1.93-31.1, P =0.007). The ORs of failure to acquire were 2.12 ( P =0.003) in patients 4 years or more versus 0 to 3 years, 4.17 ( P <0.0001) in cerebral palsy versus clubfoot, and 4.12 ( P =0.01) in short Achilles tendon versus clubfoot. There was no significant association between sex or area deprivation index and failure of brace acquisition. Conclusions: In our cohort, 7% of prescribed braces were not acquired. Black or Hispanic race, lack of insurance, and older age were associated with failure to acquire prescribed braces. Braces prescribed for clubfoot were acquired more often than for cerebral palsy or short Achilles tendon. Brace-wear compliance is an established factor in treatment success and recurrence. This study identified risk factors for failed brace acquisition, a critical step for improving compliance. These results may help effect changes in the current system that may lead to more compliance with brace wear. Level of Evidence: Level III—retrospective cohort study.